VARIASI PEMBELAJARAN MATEMATIKA DI â€œSEKOLAH â€“ RUMAHâ€ BAGI PARA HOMESCHOOLER - Abidin, Zaenal (Universitas Negeri Semarang, 2007)
Homeschooling is a relatively new term in the Indonesian education. TheDepartment of National Education (Depdiknas) officially introduces homeschooling as